El proyecto cultural liberador de José Martí para su tiempo y para el siglo xxi (2016)
In the article the validity and significance of liberating cultural project for Latin America José Martí holds. It is analyzed from the moment he was conceived in the late nineteenth century to today. The determination and defense of the views presented, it has been possible by analyzing the masterpiece of José Martí contained in the 28 volumes published in 1963 by the National Publishing House of Cuba. Textual analysis of these sources is completed by its contrast with the conditioning context of the last decades of the nineteenth century, especially in Cuba, Mexico, Guatemala, Venezuela and the United States, its contradictions and development trends. The presentation of the content of the article is structured in three sections or sections: the first, Latin America until the late nineteenth century; the second, José Martí, knowledge and Latin American vocation; and the third Marti liberating cultural project for Latin America at all times. The idea of freedom in José Martí as a vital center of the project of change and development for Latin America in which coherently it integrated cultural discourse that education, science, media and art, various manifestations integrates holds.